Phylogeography of eagle rays of the genus Aetobatus: Aetobatus narinari is restricted to the continental western Atlantic Ocean - Sales, Joao Braullio L. (2019)
The biogeography and conservation of elasmobranch species was increasingly addressed in the recent past, but the southwestern Atlantic Ocean fauna is still one of the least studied. Reliable delimitation of the distribution range of species is fundamental to conservation and development of fisheries management strategies. A recent molecular study of the cryptic Aetobatus narinari species complex restricted that species to western and eastern coasts of the New World. However, the current distribution of A. narinari and phylogenetic relationships within the genus Aetobatus have yet to be clarified, the goal of this phylogeographic analysis. Using mitochondrial and nuclear markers we investigated specimens from the Atlantic coast of Brazil and the Pacific coast of Mexico and related them to previously analyzed specimens from other regions. Our analysis indicates that Aetobatus narinari is present only in the western Atlantic, formed by a single genetic lineage that ranges between Florida and southeastern Brazil, while the Pacific New World lineage is in fact assigned to Aetobatus laticeps. Analysis of divergence times revealed that biogeographic events such as the closure of the Tethys Sea, the formation of the Benguela barrier, and the Isthmus of Panama played major roles in diversification and dispersal of the genus Aetobatus.